Xenon consumption during general surgery: a retrospective observational study - Stoppe, Christian (BioMed Central, 2013)
BACKGROUND: High costs still limits the widespread use of xenon in the clinical practice. Therefore, we evaluated xenon consumption of different delivery modes during general surgery. METHODS: A total of 48 patients that underwent general surgery with balanced xenon anaesthesia were retrospectively analysed according to the mode of xenon delivery during maintenance phase (ECO mode, AUTO mode or MANUAL mode). RESULTS: Xenon consumption was highest during the wash-in phase (9.4 ± 2.1l) and further decreased throughout maintenance of anaesthesia. Comparison of different xenon delivery modes revealed significant reduced xenon consumption during ECO mode (18.5 ± 3.7L (ECO) vs. 24.7 ± 11.5L (AUTO) vs. 29.6 ± 14.3L (MANUAL); p = 0.033). No differences could be detected with regard to anaesthetic depth, oxygenation or performance of anaesthesia. CONCLUSION: The closed-circuit respirator Felix Dual offers effective reduction of xenon consumption during general surgery when ECO mode is used.